The development of lexicon in children with hearing impairment in the context of interpreting pictures in comic-strip form - Srzić, Maja; Isaković, Ljubica; Šešum, Mia (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Pictures in the comic-strip form are often used in practice as a means of examining the development of speech and language of children with hearing impairment. Objectives. The aim of the research was to establish the development of the lexicon and the level of content comprehension of pictures in the comic-strip format in written expression of students with hearing impairment 11–15 years of age (and to establish whether the age affected students’ success and compare their results with their typical peers). Methods. A story in the comic-strip form, designed for the needs of this study, was used in the research. It comprised four pictures interconnected through the sequence of events. Each picture was allocated a number of expected answers. Results. The obtained results point to the difficulties in understanding the content of pictures in the comic-strip format in written expression of children with hearing impairment and their underdevelopment compared to their typical peers. It was observed that age had a partial effect on the development of vocabulary (no statistically significant differences) (t = -0.87, df = 122.9, p = .39). However, the trend of achievement with age was observed. Conclusion. We found that children with hearing impairment failed to understand the story, observe important elements, and comprehend the essence. The abstract side of the pictures in the series, which gives sense, was neglected, and thus, the conclusion was not made, nor was the message grasped.
Keywords: series of pictures; vocabulary; expected answers; students with hearing impairment; typical peers